Performance Comparison of Islamic Banking in Indonesia and Malaysia Islamicity Performance Index Approach - Priyono Puji Prasetyo; Pribawa E Pantas; Nurul Jihadah Ashar; Fanny Riana Pertiwi (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
This study aims to analyze the comparison of Islamic banking performance in Indonesia and Malaysia using the Islamicity Performance Index approach. This research is a quantitative study using non-statistical descriptive analysis. The research object used data from 10 banks representing Islamic banking in Indonesia and Malaysia, each taken from 5 Islamic banks with the most extensive asset ownership criteria. This research's source of data is the annual Islamic banking financial report downloaded from each Islamic bank's official website, obtained from 2015-2019. The results of the calculation of the four ratios show that Indonesian Islamic banking is superior in Profit-Sharing Ratio and Equitable Distribution Ratio, while the average score of Malaysian Islamic banking is only slightly higher in Zakat Performance Ratio and Islamic Income vs. Non-Islamic Income Ratio. Keywords: Performance, Islamic Banking, Islamicity Performance Index